Particulate matter, nitrogen oxides, ozone, and select volatile organic compounds during a winter sampling period in Logan, Utah, USA. (3rd June 2019) - Mukerjee, Shaibal; Smith, Luther; Long, Russell; Lonneman, William; Kaushik, Surender; Colon, Maribel; Oliver, Karen; Whitaker, Donald
ABSTRACT: Particulate matter mass (PM), trace gaseous pollutants, and select volatile organic compounds (VOCs) with meteorological variables were measured in Logan, Utah (Cache Valley), for >4 weeks during winter 2017 as part of the Utah Winter Fine Particle Study (UWFPS). Higher PM levels for short time periods and lower ozone (O3 ) levels were present due to meteorological and mountain valley conditions. Nitrogenous pollutants were relatively strongly correlated with PM variables. Diurnal cycles of NOx, O3, and fine PM(PM 2.5) (aerodynamic diameter <2.5 μm [PM2.5 ]) suggested formation from NOx . O3 levels increased from early morning into midafternoon, and NOx and PM2.5 increased throughout the morning, followed by sharp decreases. Toluene/benzene and xylenes/benzene ratios and VOC correlations with nitrogenous and PM species were indicative of local traffic sources. Wind sector comparisons suggested that pollutant levels were lower when winds were from nearby mountains to the east versus winds from northerly or southerly origins. Implications : The Cache Valley in Idaho and Utah has been designated a PM2.5 nonattainment area that has been attributed to air pollution buildup during winter stagnation events. To inform state implementation plans for PM2.5 in Cache Valley and other PM2.5 nonattainment areas in Utah, a state and multiagency federal research effort known as the UWFPS was conducted in winter 2017. As part of the UWFPS, the U.S. Environmental Protection Agency (EPA) measured ground-based PM species and their precursors, VOCs, and meteorology in Logan, Utah. Results reported here from the EPA study in Logan provide additional understanding of wintertime air pollution conditions and possible sources of PM and gaseous pollutants as well as being useful for future PM control strategies in this area.